Making amends in big bend /cDon Ingram. - Ingram, Don (Charleston, SC, 2009)
Buster McGruder had it all as a talendted high school football player for the Odessa Bronchos until the night in '78 when her dropped the crucial pass against cross-town rival Permian. Some believe the TD catch would have let to the first defeat of Mojo in years. Twenty years later--and a long streak of bad luck--Buster's asked to help a mother and her young daughter escape from an abusive husband while Buster's in Big Ben National Park on a not-so-noble errand. Buster's nature won't let him ignor the plea for help, but in doing so his goal is altered and his own life is put in jeopardy. The rock slide in Santa Elena Canyon on the Rio Grande proves to be the backdrop for a deadly confrontation as the former star attempts to make amends in Big Bend.
Keywords: Fiction -- Texas